CONSUMERISM PRACTICES OF KOREAN POP FANS COMMUNITY ANNISA WIDOWATI SUNDARI DANCERS IN JAKARTA - Apria, Diana Rosca; Kumbara, A.A. Anom; Darma Putra, I Nyoman (E-Journal of Cultural Studies; Volume 13, Number 4, November 2020, 2020)
Globalization facilitates the spread of culture from one country to another. From globalization, K-Pop has finally begun to be enjoyed by Indonesian society. One of the effects of the Korean culture fever in Indonesia is the consumptive behavior or lifestyle among teenagers who are K-Pop fans. Annisa Widowati Sundari Dancers Community or what is commonly called as AWS Dancers community is one of them. The reason why this community has been chosen as the object of this research is because AWS Dancers community is popular among K-Pop fans in Jakarta. This study used a cultural study approach that is analyzed qualitatively. Data collection is carried out by the method of observation, interviews, and document studies related to K-pop culture in Indonesia. Data were analyzed with hegemony theory and culture industry theory. The results of this study show that the emergence of the K-Pop culture industry ultimately inspired K-Pop fans to form a community, namely AWS Dancers who performed dance cover activities. In addition, K-Pop culture industries such as music, drama, food, cosmetics and electronic goods made teenagers who are members of the AWS Dancers community was hegemonied to buy and consume these things. As a result, various implications arise, such as dissipation among the members of AWS Dancers, hyperreality towards South Korea, the increasingly eroded Indonesian culture and celebritization among members of the AWS Dancers community. Keywords : consumerism practices, korean pop, AWS community, hegemony, culture industry